2015
DOI: 10.7314/apjcp.2015.16.9.3747
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fibre and the Risk of Colorectal Cancer: a Case-Control Study

Abstract: Background: Colorectal cancer is one of the most commonly occurring cancers in China. Dietary fibre has been thought to decrease the risk of colorectal cancer in Western countries. However, studies investigating the association between dietary fibre (particularly soluble and insoluble fibres) and colorectal cancer have hitherto been lacking in China. Objective: This case-control study examined the effect of dietary fibre intake on the risk of colorectal cancer, stratified by tumour site. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 39 publications
1
24
0
3
Order By: Relevance
“…In our investigation, the consumption of bread and white rice was associated with increased risk for intestinal carcinogenesis. In the other hand, the consumption of bread and brown rice had a protective effect, in agreement with other related epidemiological studies [8] [56].…”
Section: Dietary Variablessupporting
confidence: 92%
“…In our investigation, the consumption of bread and white rice was associated with increased risk for intestinal carcinogenesis. In the other hand, the consumption of bread and brown rice had a protective effect, in agreement with other related epidemiological studies [8] [56].…”
Section: Dietary Variablessupporting
confidence: 92%
“…Beberapa penelitian sebelumnya telah menunjukkan bahwa serat makanan dikaitkan dengan pengurangan risiko kanker kolorektal. (8)(9)(10) Tetapi hasil lainnya tidak menemukan efek serat dalam penurunan risiko kanker kolorektal. (11,12) Beberapa hasil penelitian ini menggambarkan tidak selalu konsistennya hasil yang didapatkan mengenai pengaruh serat terhadap kanker kolorektal.…”
Section: Pendahuluanunclassified
“…Asupan serat yang tinggi, terutama dari sereal atau biji-bijian dan buah-buahan, dikaitkan dengan penurunan risiko insiden kanker kolorektal. (8,12,20) Studi prospektif dalam uji skrining berbasis populasi menunjukkan bahwa individu yang mengonsumsi asupan serat makanan tertinggi telah mengurangi risiko insiden kanker kolorektal. (11) Sumber serat dari buah, sayuran, kacang-kacangan, sereal dan biji-bijian.…”
Section: Pembahasanunclassified
“…A case‐control study in China consisting of 265 CRC patients and 252 controls showed that the amount of red meat and processed poultry meat intake was not significantly correlated with the development of CRC. Shao et al summarized the case‐control studies on risk factors for CRC in China and a meta‐analysis of the data from 6646 CRC patients and 9957 controls showed that red meat consumption was a risk factor for CRC (OR 1.62, 95% CI 1.27–2.07).…”
Section: Primary Prevention Of Sporadic Cramentioning
confidence: 99%